2019
DOI: 10.1016/j.molmet.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary sucrose on adiposity and glucose homeostasis in C57BL/6J mice depends on mode of ingestion: liquid or solid

Abstract: Objective Although it is widely accepted that obesity results from an imbalance of energy intake and expenditure, the mechanisms underlying this process and effective strategies for prevention and treatment are unclear. Growing evidence suggests excess consumption of sugar may play an important role, yet we showed previously in mice that consuming up to 30% of calories as sucrose in the diet had no impact on weight regulation. Since in humans consumption of sugar-sweetened beverages has been widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 41 publications
12
59
0
1
Order By: Relevance
“…In addition to the effects we observed on lipid metabolism, we ( Figure 1D and Supplementary Figure 1) and others (Burke et al, 2018;Maekawa et al, 2017;Togo et al, 2019) have shown that energy expenditure increases in response to liquid sucrose intake. Given our observation of a disconnect between energy intake, energy expenditure and adiposity in the absence of any impairments to systemic insulin sensitivity following chronic liquid sucrose intake, we sought to determine if microbial metabolism might explain some of these metabolic adaptations.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In addition to the effects we observed on lipid metabolism, we ( Figure 1D and Supplementary Figure 1) and others (Burke et al, 2018;Maekawa et al, 2017;Togo et al, 2019) have shown that energy expenditure increases in response to liquid sucrose intake. Given our observation of a disconnect between energy intake, energy expenditure and adiposity in the absence of any impairments to systemic insulin sensitivity following chronic liquid sucrose intake, we sought to determine if microbial metabolism might explain some of these metabolic adaptations.…”
Section: Discussionsupporting
confidence: 79%
“…Although dietary sugars have been used extensively to induce cardiometabolic abnormalities in animal models (Bacon et al, 1984;Bukowiecki et al, 1983;Burke et al, 2018;Chen et al, 2019;Kawasaki et al, 2009;Oliveira et al, 2014;Ritze et al, 2014;Softic et al, 2019;Togo et al, 2019), the molecular mechanisms underlying sugar-induced hepatic lipid accumulation remain poorly understood in a context that is translational to human dietary practices (Choo and Sievenpiper, 2015). Most preclinical studies rely upon use of supraphysiologic concentrations of sucrose, glucose or fructose to induce steatosis and other metabolic comorbidities (Chen et al, 2011;Choo and Sievenpiper, 2015;Softic et al, 2019;Soria et al, 2001), often with the confounding addition of excess dietary lipid (Chen et al, 2011;Oliveira et al, 2014;Softic et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…75 84 Furthermore, a study using male C57BL/6J mice (8 weeks old) suggested that distinct modes of sucrose delivery differentially affected body regulation and glucose homeostasis. 134 The authors showed that mice exposed to a liquid sucrose solution (50% sucrose in the water plus 30% calories from sucrose in solid food)…”
Section: Prediabetesmentioning
confidence: 99%